UPAYA MENINGKATKAN HASIL BELAJAR TEMATIK TEMA 6 MELALUI PENDEKATAN SAINTIFIK PADA SISWA KELAS III SD NEGERI 01 KLEGEN KOTA MADIUN - Chrisna Sujatmiko; Dwi Nilla Andriani; Purwati, Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This classroom action research aimed to improve thematic learning outcomes for theme 6 through a scientific approach for 3rd grade students at SDN 01 Klegen, Madiun City. The subjects of this research were 20 class III students at SDN 01 Klegen, Madiun City. This research was Classroom Action Research (PTK) which was carried out in two cycles. Each cycle included 4 (four) stages, namely planning, implementing actions, observation and reflection. This research used a cycle method consisting of 2 cycles, namely cycle I and cycle II. The data collection techniques used were observation, interviews and tests. The results of the research showed that applying a scientific approach can improve thematic learning outcomes for theme 6 in 3rd grade at SDN 01 Klegen, Madiun City. This was proved by an increase in the average value of student learning outcomes from 68.50 in cycle I to 82.00 in cycle II.